Exploration of factors affecting the use of Web 2.0 for knowledge sharing among healthcare professionals: an Indian perspective. Issue 3 (23rd September 2020) - Maheshwari, Bhawana; Sarrion, Miguel; Motiani, Manoj; O'Sullivan, Siobhan; Chandwani, Rajesh
Abstract : Purpose: This study aims to explore knowledge sharing (KS) attitudes and intention of healthcare professionals in India through the use of information and communication technology platforms such as Web 2.0. The research specifically focuses on individual motivators such as the face, reputation and reciprocity, which, to an extent, are influenced by indigenous culture. Design/methodology/approach: The study uses a cross-sectional survey design to collect data. A sample of 207 was obtained from professionals working in healthcare in India. The data were analyzed using the partial least square-structural equation modeling. Findings: The results confirmed that attitude toward KS leads to the intention to share knowledge. Attitude toward KS using Web 2.0 was found to be positively related to self-efficacy and reciprocity. Furthermore, face and reputation were found to moderate the relationship between attitude and intention to share knowledge while the moderating effect of rewards was found to be insignificant. Research limitations/implications: This study was limited to healthcare professionals in India. Knowledge workers in other industries can be considered for further studies. Practical implications: This study provides useful insights into KS practices using Web 2.0 among knowledge workers. Particularly it emphasizes the individual motivators, which can be manipulated by Web 2.0 designers to nurture a positive attitude toward KS and to encourage user's participation. Originality/value: The study investigates, using an integrated theoretical framework, how certain factors act as a motivator or a barrier for sharing knowledge using Web 2.0. in the specific cultural context of healthcare professionals in India.